2012
DOI: 10.1016/j.tjog.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Topical imiquimod treatment for human papillomavirus infection in patients with and without cervical/vaginal intraepithelial neoplasia

Abstract: The tolerability of intravaginal self-administered imiquimod is confirmed. Its efficacy in the treatment of women with persistent HPV infection and normal cytology warrants further randomized, controlled trials to determine appropriate dosages and scheduling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 29 publications
0
51
0
5
Order By: Relevance
“…Both VIN and VAIN are HPV-related neoplasia and the pathophysiology is comparable to CIN. Previous studies have investigated the effect of imiquimod in CIN and showed the adverse effects to be well-tolerated [4,5]. Currently, a non-randomised study comparing the effectiveness of imiquimod treatment with large loop excision of the transformation zone (LLETZ) is being performed in the Netherlands (TOPIC-3) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Both VIN and VAIN are HPV-related neoplasia and the pathophysiology is comparable to CIN. Previous studies have investigated the effect of imiquimod in CIN and showed the adverse effects to be well-tolerated [4,5]. Currently, a non-randomised study comparing the effectiveness of imiquimod treatment with large loop excision of the transformation zone (LLETZ) is being performed in the Netherlands (TOPIC-3) [6].…”
Section: Introductionmentioning
confidence: 99%
“…A 57% complete response rate was reported during median follow‐up of 18.4 months, which is in line with our results of complete histological regression rate of 70% in a shorter follow‐up period. Two retrospective studies with self‐administered imiquimod cream comprised mainly of VAIN 1 patients, with regression rates of 86% ( n = 42) and 54% ( n = 26), respectively . The study by Lin et al .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 The use of Imiquimod for the treatment of CIN2/3 or VIN2/3 has shown limited clinical benefits and topical application was more or less well tolerated depending on the study. [25][26][27] Why therapeutic vaccines have shown limited efficacy against HPV associated neoplasia Multiple reasons could explain the limited success of therapeutic vaccines against HPV-induced neoplasia to date. Numerous clinical trials have shown induction of T cell responses against E6 and E7, but the magnitude of the response induced against HPV antigens might have been insufficient to clear HPV infected or transformed cells.…”
Section: Clinical Evaluation Of Immunotherapeutic Interventions Againmentioning
confidence: 99%